Impact and cost-benefit analysis: A unifying approach - Pasquale Lucio Scandizzo (Journal of Economic Structures, 2021)
This paper presents a methodology to integrate cost-benefit analysis and SAM-CGE-based impact evaluation. While the two types of analysis have developed in parallel and without a clear connection, there is growing consensus that the two approaches should be integrated for complex investment projects, since their economic evaluation cannot rely solely on the partial equilibrium assumptions of cost-benefit (CB) analysis. Unlike CB analysis, impact evaluation looks at the economy as a complete system of interdependent components (industries, households, investors, government, importers, exporters). By integrating project accounting into a SAM-CGE framework, the methodology developed presents several properties that make it fit to the purpose of providing a reliable assessment of project contribution to the economy.
Keywords: D57; D58; D62; E17; F35; O22; 330; Benefit analysis; Computable general equilibrium models (CGE); Cost; Evaluation; Impact analysis; Project; Social accounting matrix (SAM)